Lexical and Structural Cues to Discourse Processing in First and Second Language - Crible, Ludivine; Wetzel, Mathis; Zufferey, Sandrine (Frontiers in Psychology, 2021)
Discourse connectives are lexical items like ‘but’ and ‘so’ that are well-known to influence the online processing of the discourse relations they convey. Yet, discourse relations like causality or contrast can also be signalled by other means than connectives, such as syntactic structures. So far, the influence of these alternative signals for discourse processing has been comparatively under-researched. In particular, their processing in a second language remains entirely unexplored. In a series of three self-paced reading experiments, we compare the reading patterns of contrastive relations by native French-speakers and non-native speakers of French with English as a first language. We focus on the effect of syntactic parallelism and how it interacts with different types of connectives. We test whether native and non-native readers equally recruit parallelism to process contrast in combination with or without a connective (Experiment 1), with a frequent vs. infrequent connective (Experiment 2) and with an ambiguous vs. unambiguous connective (Experiment 3), thus varying the explicitness and ease of retrieval of the contrast relation. Our results indicate that parallelism plays an important role for both groups of readers, but that it is a more prominent cue for non-native speakers, while its effect is modulated by task difficulty for native participants.